2021
DOI: 10.3390/ijms22189683
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Mono- and Bi-Transgenic Pig-Derived Epidermal Keratinocytes Expressing Human FUT2 and GLA Genes—In Vitro Studies

Abstract: Pig-to-human xenotransplantation seems to be the response to the contemporary shortage of tissue/organ donors. Unfortunately, the phylogenetic distance between pig and human implies hyperacute xenograft rejection. In this study, we tested the hypothesis that combining expression of human α1,2-fucosyltransferase (hFUT2) and α-galactosidase A (hGLA) genes would allow for removal of this obstacle in porcine transgenic epidermal keratinocytes (PEKs). We sought to determine not only the expression profiles of recom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 38 publications
2
21
0
Order By: Relevance
“…Despite effective knockdown, 5.87% of embryos was able to develop into blastocysts, possibly due to the presence of maternally contributed FOLR1 which may eventually exhausted until blastocyst stage. Our results are in line with a previous study (Strandgaard et al, 2017), which demonstrated the compromised ability of mouse embryos to develop to blastocyst stage after TA B L E 1 Effect of FOLR1 knockdown on the rate of blastocyst production injection (Kharche et al, 2016;Magata et al, 2019;Menéndez-Blanco et al, 2020;Shirazi et al, 2018) and cloning by somatic cell nuclear transfer (Gorczyca et al, 2021;Hernández Martínez et al, 2020;Samiec et al, 2019;Skrzyszowska & Samiec, 2020Wiater et al, 2021).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Despite effective knockdown, 5.87% of embryos was able to develop into blastocysts, possibly due to the presence of maternally contributed FOLR1 which may eventually exhausted until blastocyst stage. Our results are in line with a previous study (Strandgaard et al, 2017), which demonstrated the compromised ability of mouse embryos to develop to blastocyst stage after TA B L E 1 Effect of FOLR1 knockdown on the rate of blastocyst production injection (Kharche et al, 2016;Magata et al, 2019;Menéndez-Blanco et al, 2020;Shirazi et al, 2018) and cloning by somatic cell nuclear transfer (Gorczyca et al, 2021;Hernández Martínez et al, 2020;Samiec et al, 2019;Skrzyszowska & Samiec, 2020Wiater et al, 2021).…”
Section: Discussionsupporting
confidence: 92%
“…The future studies at our laboratory may decipher some of these questions in order to thoroughly elucidate the importance of FOLR1 as a pivotal biomarker suitable for prediction of augmented susceptibility of embryonic genomes to efficient epigenetic reprogramming of their transcriptional activities. The latter could enable the embryologists to estimate the increased developmental competences and molecular quality of caprine and other mammalian species embryos produced by such modern assisted reproductive technologies as microsurgical IVF by intracytoplasmic sperm injection (Kharche et al., 2016; Magata et al., 2019; Menéndez‐Blanco et al., 2020; Shirazi et al., 2018) and cloning by somatic cell nuclear transfer (Gorczyca et al., 2021; Hernández Martínez et al., 2020; Samiec et al., 2019; Skrzyszowska & Samiec, 2020, 2021; Wiater et al., 2021).…”
Section: Discussionmentioning
confidence: 99%
“…The results of the current research have proven that designing modern and powerful approaches to the murine ex vivo 3D model of IGF-1-assisted growth and maturation of ovarian secondary preantral follicles in order to obtain satisfactory outcomes of IVM might be reliable and feasible for the purposes of achieving high efficiency rates in such novel ARTs as IVF/ICSI in humans and other mammalian species [ 65 , 66 , 67 , 68 ] or somatic cell cloning in other mammalian species [ 69 , 70 , 71 , 72 ].…”
Section: Discussionmentioning
confidence: 99%
“…Collectively, the results of the current investigation aimed to devise and optimize intracellular strain-related parameters that turned out to vary depending on different speeds of penetrating the porcine oocytes with the use of robotic (i.e., motorized) micro-manipulators might contribute to improvement of the efficiency of a variety of modern assisted reproductive technologies (ARTs). Taking the above-mentioned findings into consideration, the augmented efficiencies of microsurgical in vitro fertilization by ICSI and cloning by somatic cell nuclear transfer (SCNT) will be of especially great importance not only in pigs but also in other mammalian species [25][26][27][28][29][30][31].…”
Section: Discussionmentioning
confidence: 99%